PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS E-COMMERCE STUDI KASUS TOKO KUN JAKARTA - Handayani, Sutri (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2018)
Information technology is very influential for the progress of a business. Various ways are done to promote the business owned, one of them by using ecommerce website. E-commerce is a buying and selling activity conducted online through the website or website. In KUN Toko case study case, the problem that often faced is the promotion media using only banners, the sale is still limited to offline, data storage and printing report is still in the form of records in the form of archives. The purpose of the research is to provide solutions to solve existing problems by designing an ecommerce-based sales information system. The results and conclusions of this research is ecommerce-based sales website can be used as a media campaign, simplify the process of selling done online, and can simplify the data processing and printing reports that no longer require recording in the form of archives.